Five-loop fermion anomalous dimension for a general gauge group from four-loop massless propagators - P.A. Baikov; K.G. Chetyrkin; J.H. Kühn (Journal of High Energy Physics, 2017)
Abstract We extend the O α s 5 $$ \mathcal{O}\left(α_s^5\right) $$ result of the analytic calculation of the quark mass anomalous dimension in pQCD [1] to the case of a generic gauge group. We present explicit formulas which express the relevant renormalization constants in terms of four-loop massless propagators. We also use our result to shed new light on the old puzzle of the absence of even zetas in results of perturbative calculations for a class of physical observables.